Supplemental Vitamin B-12 Enhances the Neural Response to Sensory Stimulation in the Barrel Cortex of Healthy Rats but Does Not Affect Spontaneous Neural Activity. Issue 5 (22nd April 2019) - Kang, Sungmin; Hayashi, Yurie; Bruyns-Haylett, Michael; Baker, Daniel H; Boura, Marcia; Wang, Xuedan; Karatzas, Kimon-Andreas; Serra, Ines; Bithell, Angela; Williams, Claire; Field, David T; Zheng, Ying
ABSTRACT: Background: Although vitamin B-12 (B-12) is known to contribute to the structural and functional development of the brain, it is unclear if B-12 supplementation has any beneficial effect in healthy populations in terms of enhanced neurologic status of the brain or improved cognitive function. Objectives: We investigated the effect of dietary supplementation of B-12 on the cortical neural activity of well-nourished young adult rats and tested the hypothesis that B-12 supplementation in healthy rats may reduce sensory-evoked neural activity due to enhanced inhibition. Methods: Female Lister Hooded rats weighing 190–265 g (2–4 mo old) were included in the study. The experimental group was fed with B-12 (cyanocobalamin)–enriched water at a concentration of 1 mg/L, and the control (CON) group with tap water for 3 wk. Animals were then anesthetized and cortical neural responses to whisker stimulation were recorded in vivo through the use of a multichannel microelectrode, from which local field potentials (LFPs) were extracted. Results: Somatosensory-evoked LFP was 25% larger in the B-12 group (4.13 ± 0.24 mV) than in the CON group (3.30 ± 0.21 mV) ( P  = 0.02). Spontaneous neural activity did not differ between groups; frequency spectra at each frequency bin of interest did not pass the cluster-forming threshold at the 5% significance level. Conclusions: These findings do not provide evidence supporting the hypothesis of decreased neural activity due to B-12 supplementation. As the spontaneous neural activity was unaffected, the increase in somatosensory-evoked LFP may be due to enhanced afferent signal reaching the barrel cortex from the whisker pad, indicating that B-12–supplemented rats may have enhanced sensitivity to sensory stimulation compared with the CON group. We suggest that this enhancement might be the result of lowered sensory threshold, although the underlying mechanism has yet to be elucidated.